A "Just Enough" Gross Proximal Margin Length Ensuring Pathologically Complete Resection in Distal Gastrectomy for Gastric Cancer. Issue 2 (11th December 2020) - Hayami, Masaru; Ohashi, Manabu; Ida, Satoshi; Kumagai, Koshi; Sano, Takeshi; Hiki, Naoki; Nunobe, Souya
Abstract : Introduction: The objective of this study is to determine a "just enough" gross proximal margin (PM) length to ensure a pathologically negative PM in distal gastrectomy for gastric cancer. There is a discrepancy between the gross and pathological proximal boundaries of gastric cancer. We must transect the stomach maintaining some safety margins to obtain a pathologically negative PM. However, we have no standard to indicate where to transect the stomach. Methods: Patients undergoing distal gastrectomy for gastric cancer were enrolled. A new parameter named ΔPM, which corresponded to the pathological extension proximal to the gross tumor boundary toward the resection stump, was evaluated. The number of patients was counted in each ΔPM range of 1-cm increments. The maximum ΔPM was defined as the first value at which the number of patients became 0, and it was determined as the recommended gross PM length for each disease type. Results: In cT1, 259 and 330 patients were assigned to differentiated (Dif) and undifferentiated types (Und), respectively. The maximum ΔPM was 20 mm for Dif and 40 mm for Und. In cT2–4, 194 and 490 patients were assigned to the expansive (Exp) and infiltrative (Inf) growth types. The maximum ΔPM was 30 mm for Exp. The maximum ΔPM was 50 mm for Inf of less than 80 mm and 60 mm for Inf of 80 mm or more. Conclusions: A newly recommended gross PM length to ensure pathologically negative PMs in distal gastrectomy for each gastric cancer type was determined. Abstract : Mini-abstract: The pathological extension proximal to the gross tumor boundary was evaluated using a novel parameter, ΔPM, to determine a "just enough" gross proximal margin length in distal gastrectomy for gastric cancer. A gross proximal margin length was recommended for each disease type to obtain a pathologically negative margin.